2003
DOI: 10.1136/bjo.87.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Severe interferon associated retinopathy

Abstract: The caruncle has a non-keratinised epithelial lining similar to the conjunctival epithelium. However, unlike the conjunctiva, the caruncle harbours skin elements such as hair follicles, sebaceous glands, sweat glands, and accessory Case reportA 26 year old woman presented with a 2 mm, asymptomatic, pale yellow lesion of the right caruncle, present for 8 months (Fig 1). It was excised intact under local anaesthetic and histological examination revealed a cyst lined by stratified squamous epithelium and conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 6 publications
0
21
0
2
Order By: Relevance
“…This is thought to increase leukocyte adhesion, which may trigger microcirculation obstruction (1)(2)(3) . Furthermore, it has been reported that IFN induces thrombogenic antibody proliferation (9) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is thought to increase leukocyte adhesion, which may trigger microcirculation obstruction (1)(2)(3) . Furthermore, it has been reported that IFN induces thrombogenic antibody proliferation (9) .…”
Section: Discussionmentioning
confidence: 99%
“…The most common side effects are fever, myalgia, arthralgia, and headache. Retinal damage may also be associated with its use (2,3) . Furthermore, more serious disorders such as neurologic alterations, hepatotoxicity, and hematopoietic or cardiovascular irregularities, have been associated with IFN treatment (2,3) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the percentage of patients with hypertension and diabetes mellitus was small, and this may have contributed to our inability to detect significant differences between the retinopathy and no-retinopathy groups. However, previous reports have shown that a history of hypertension or diabetes mellitus is a risk factor for retinopathy [15,16]. In particular, a history of diabetes mellitus tends to be more prevalent in hepatitis patients than in the general population, and negative prognostic factors for hepatitis and hepatocellular cancer and hypertension have been identified as factors related to systemic atherosclerotic complications in hepatitis patients [21,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes and hypertension appear to be at particular risk for developing retinopathy during IFN therapy, and this is probably related to preexisting disturbances in their retinal microcirculation. Consequently, in these higher-risk patients, where severe retinal damage carries a risk of visual loss, ophthalmologic evaluations are recommended prior to and during IFN therapy [1,15,16]. …”
Section: Discussionmentioning
confidence: 99%